(untitled) (Acta Scientiarum. Agronomy, 2011)
One hundred forty-four microorganisms previously isolated from coffee fruit (Coffea Arabica) were grown on casein agar to evaluate their proteolytic activities. Fifty percent of filamentous fungi, 52.5% of bacteria and 2.6% of yeasts were able to secrete proteases. Positive isolates were further examined in liquid culture for their protease activities by hydrolysis of casein at different pH values (5.0, 7.0 and 9.0) at 30 oC. Bacillus megaterium, B. subtilis, Enterobacter agglomerans, Kurthia sp, Pseudomonas paucimobilis and Tatumella ptyseos demonstrated the highest proteolytic activities at pH 9.0. One yeast isolate, Citeromyces matritensis, had a proteolytic activity of 2.40 U at pH 5.0. Aspergillus dimorphicus, A. ochraceus, Fusarium moniliforme, F. solani, Penicillium fellutanum and P. waksmanii showed the highest activities. Of the bacterial isolates, the highest enzyme activities were observed in B. subtilis 333 (27.1 U), Tatumella ptyseos (27.0 U) and B. megaterium 817 (26.2 U). Of the filamentous fungi, Aspergillus ochraceus (48.7 U), Fusarium moniliforme 221 (37.5 U) and F. solani 359 (37.4 U) had the highest activities at pH 9.0.